A dry and fully dispersible bacterial cellulose formulation as a stabilizer for oil-in-water emulsions. (15th February 2020) - Martins, D.; Estevinho, B.; Rocha, F.; Dourado, F.; Gama, M.
Graphical abstract: Highlights: Bacterial Cellulose was fully redispersed after co-drying with carboxymethyl cellulose. The formulation was able to effectively stabilize an isohexadecane-in-water emulsion. Bacterial Cellulose fibre networks structuring the emulsion were observed. The formulation performed better than plant celluloses, and similarly to xanthan. The bacterial cellulose formulation was able to lower the oil/water interface tension. Abstract: Bacterial cellulose (BC) is an emerging alternative to plant cellulose in different applications. Several works demonstrated the potential of never-dried BC; however, envisioning real industrial applications, a dry product retaining its functional properties upon rehydration is preferable. A dry and completely redispersible formulation of BC with carboxymethyl cellulose (CMC) was prepared by Spray-drying. The obtained material showed a Zeta Potential of (-67.0 ± 3.9) mV, a Dv(50) of (601 ± 19.7) μm and was able to decrease the oil/water interface energy. The dry BC:CMC formulation was employed as a stabilizer in oil-in-water emulsions, in parallel with commercial plant celluloses and Xanthan gum. The emulsions were monitored over time by optical microscopy and characterized by rheological measurements. BC:CMC effectively stabilized emulsions against coalescence and creaming, at a concentration of 0.50 % - contrarily to other commercial dry celluloses – due to the Pickering effect and to the structuring of the continuous phase, as seen with Cryo-SEM.